Postdigital cultural studies. (July 2020) - Murray, Sarah
What should a postdigital cultural studies look like? Identifying economies of attention is central to the study of media and culture. Calling for renewed focus on attention as power, this article pairs three long-established lessons of cultural studies with three examples of contemporary digital immersion: deepfakes and manipulated media; algorithmic culture; and, the digital afterlife industry. In doing so, the critical questions that drive cultural studies emerge as ever relevant in a postdigital, post-truth landscape.